Analisis Disfemia Pada Kolom Berita Olahraga Surat Kabar Tempo Edisi Februari 2016 Sebagai Bahan Ajar Bahasa Indonesia Di Sma/K - , Nurhayati; , Prof. Dr. Abdul Ngalim, M.M.,M.Hum (2016)
Interest empirically is to identify the form of the use of disfemia contained in the news column newspaper Tempo in February 2016, describes the value of taste contained in the use disfemia column sports news newspaper Tempo in February 2016, and describe the form of the use of disfemia as teaching materials Indonesian in SM/K. The method used in this research is descriptive qualitative. Sources of data obtained from the February issue of sports news columns 2016. Techniques used in data collection techniques followed by technical documentation see and note. Analysis of the data in this study using the referential, pragmati and HBS, while also mengguanakn method agih dressing techniques. The results showed (1) form disfemia usage in news columns Tempo newspaper in February 2016 are grouped into three. Words, such as cutting, rolling, bought up. Phrases, such as mengelembungkan nose. (2) Value flavors contained in disfemia usage in news columns Tempo newspaper in February 2016 that is. a) creepy, like boxed forbidden, couples death; b) terrible, like silence, destroy; scary like, cut, loss of teeth; d) repugnant, such as drooping; e) terrible, like wrapping the armband dilengan. (3) the results of this study are impliksi on learning as teaching materials Indonesian at SMA / K and ethics learning to speak to shape the character of self-learners.